Abdominal Fat is a Reliable Indicator of Lumbar Intervertebral Disc Degeneration than Body Mass Index - Wang, Minglang; Yuan, Hao; Lei, Fei; zhang, Shilin; Jiang, Lin; Yan, Jiyuan; Feng, Daxiong (World neurosurgery, 2024)
The objective of this study was to determine whether abdominal fat status correlates with low back pain (LBP) and lumbar intervertebral disc degeneration (IVDD) and to identify a new anthropometric index to predict the likelihood of developing LBP. Patients with chronic low back pain admitted to the Affiliated Hospital of Southwest Medical University from June 2022 to May 2023 were collected as the experimental group. Volunteers without LBP from June 2022 to May 2023 were also recruited as the control group. They underwent lumbar spine magnetic resonance imaging and had their body mass index (BMI) measured. Abdominal parameters were measured on T2-weighted median sagittal magnetic resonance imaging at the L3/4 level: abdominal diameter, sagittal abdominal diameter (SAD), and subcutaneous abdominal fat thickness (SAFT). Each lumbar IVDD was assessed using the Pfirrmann grading system. The differences in abdominal parameters and BMI between the experimental and control groups were compared, and the correlations between abdominal parameters, BMI, LBP, and IVDD were analyzed. Abdominal diameter, SAD, and SAFT had moderate-to-strong correlations with BMI. SAD was significantly associated with severe IVDD at L4-L5 and L5-S1 levels with odds ratio of 3.201 (95% confidence interval [CI]: 1.850–5.539, P < 0.001) and 1.596 (95% CI: 1.072–2.378, P = 0.021), respectively. BMI had no significant association with severe IVDD. In women, SAFT and BMI were significantly correlated with LBP; in men, only SAFT was significantly correlated with LBP. Appropriate cutoff values for men and women were 1.52 cm (area under the curve = 0.702, 95% CI: 0.615–0.789, P < 0.001) and 1.97 cm (area under the curve = 0.740, 95% CI: 0.662–0.818, P < 0.001), respectively. Men and women with SAFT of >1.52 cm and >1.97 cm, respectively, had significantly higher rates of LBP. SAD could predict severe IVDD better than BMI. SAFT is a better predictor of LBP than BMI, especially in men, and reliably distinguished patients with LBP from asymptomatic subjects with reliable cutoff values for men and women.